FRI0551 IDENTIFYING RESEARCH PRIORITIES FOR JUVENILE IDIOPATHIC ARTHRITIS TOGETHER WITH PATIENTS, CARERS AND CLINICIANS THROUGH THE JAMES LIND ALLIANCE METHOD: PRELIMINARY RESULTS. (June 2019) - Verwoerd, Anouk; Armbrust, Wineke; Cowan, Katherine; Olsder, Wendy; Cappon, Jeannette; Schoemaker, Casper
Abstract : Background: Research on Juvenile Idiopathic Arthritis (JIA) should have the primary goal to ultimately improve the lives of the affected patients, and help health professionals provide the best care for them. Therefore, these end users of research evidence – patients, carers (parents/caregivers) and clinicians – should be included in the process of identifying research priorities. Importantly, patients and carers can use their unique experiential knowledge from living with the disease to give vital input to researchers in designing a study. Combining this input with the goal of research(ers) to make a true impact on patients' lives, will result in research that is more effective and meaningful, and thereby increases research value [1]. To this end, we initiated the project of establishing a research agenda for JIA jointly by patients, carers and clinicians [2]. Objectives: The objective of this project is to bring patients, carers and clinicians together to identify research priorities and create a research agenda for JIA, such that future research into JIA is guided to the issues that matter most. Methods: The method for research priority setting developed by the James Lind Alliance (JLA) is used [3]. This method consists of several steps with the end goal of creating a top 10 list of research priorities agreed on by all parties. First, a steering group with equal representation of patients, parents and clinicians was assembled. We are now in the process of collecting research questions through an online survey. Focus groups are being held to ensure the inclusion of younger patients. Questions will be clustered and checked against the evidence. Next, the process of interim priority setting will follow, in which a shortlist of up to 30 questions will be assembled. During a final workshop in which all parties are equally represented, the top 10 research priorities will be established. This workshop is scheduled for the end of 2019. A process evaluation is conducted to monitor ethical aspects in the decision-making process. Results: The first step of collecting research questions is performed until the end of March 2019. We will be able to present preliminary results on the questions gathered from the online survey and focus groups by June 2019. Furthermore, we will discuss the effects of our efforts to be inclusive and representative of every party involved. Conclusion: Through this project, patients, carers and clinicians are brought together to define the most important unanswered questions for JIA. Engaging patients and stakeholders in this crucial phase is the next step in performing more meaningful and effective research. References: [1] Chalmers I, Bracken MB, Djulbegovic BD, et al. How to increase value and reduce waste when research priorities are set. Lancet2014; 383;156-165. [2] Schoemaker CG, Armbrust W, Swart JF, et al. Dutch juvenile idiopathic arthritis patients, carers and clinicians create a research agenda together following the James Lind Alliance method: a study protocol. Pediatr Rheumatol Online J2018;16(1):57. [3] James Lind Alliance. Guidebook. 2018; Available from: www.jla.nihr.ac.uk/jla-guidebook.Accessed 4 January 2018. Acknowledgement: We thank all the members on the steering group of the JIA Priority Setting Partnership. Disclosure of Interests: None declared